Miliary Sarcoidosis: does it exist? A case series and systematic review of literature - Rajagopala, Srinivas; Shankari, Sakthi; Kancherla, Roopa; Ramanathan, Ramanathan Palaniappan; Balalakshmoji, Devanand (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background and Objectives: Sarcoidosis typically presents with peribronchovascular and perilymphatic nodules on high-resolution computed tomography (HRCT); a miliary pattern is reported but not well described. Design, setting: We describe four patients with miliary sarcoidosis and results of a systematic review of all previously reported cases from 1985 onwards. Results: We identified only 27 cases of “miliary” sarcoidosis in the HRCT era. These patients were older (85.2% older than 40 years), had more co-morbidities (72.7%) and were symptomatic compared to “typical” sarcoidosis. Respiratory symptoms were present in 61.9% at diagnosis. Hypercalcemia was seen in 28.5%. On review of HRCT images, only 34.6% (9/26) had a “true miliary” pattern without fissural nodules. In our series, prominent perivascular granulomas were seen on histopathology in all. 44.4% (12/27) had tuberculosis preceding or concurrent to miliary sarcoidosis. Of the eight true associations, tuberculosis preceded sarcoidosis by 52 (median, IQR 36) weeks in six and occurred concurrently in another two. The diagnosis of tuberculosis was clinical in all with concurrent diagnosis of tuberculosis and sarcoidosis. Treatment with steroids had 100% response and 14.2% relapse. Conclusions: A true miliary pattern in the HRCT era is very rare in sarcoidosis and subtle perilymphatic pattern is nearly always seen; this should be labeled “pseudo-miliary”. Prominent perivascular granulomas are associated with true miliary pattern. Miliary sarcoidosis patients are older and symptomatic, needing treatment at diagnosis. “Miliary” sarcoidosis may follow treatment for tuberculosis; concurrent cases possibly indicate the difficulty in differentiating both or a “tuberculo-sarcoid” presentation.